Relative importance of physiological, anthropometric, and skill qualities to team selection in professional rugby league - Gabbett, T. J.; Jenkins, D. G.; Abernethy, B. (Journal of Sports Sciences, 2011)
This study investigated the relative importance of physiological, anthropometric, and skill qualities to team selection in professional rugby league. Eighty-six high performance rugby league players underwent measurements of anthropometric (height, body mass, sum of seven skinfolds), physiological (speed, change of direction speed, lower body muscular power, repeated-sprint ability, prolonged high-intensity intermittent running ability, and maximal aerobic power), technical skill (tackling proficiency, draw and pass proficiency), and perceptual skill (reactive agility, pattern recall, pattern prediction) qualities. A linear discriminant analysis was also conducted comparing those players successful in gaining selection into the professional National Rugby League team with those not selected to determine which, if any, of these qualities could predict selection. Players selected to play in the first National Rugby League game of the season were older, more experienced, leaner, had faster 10m and 40m sprint times, and superior vertical jump performances, maximal aerobic power, tackling proficiency and dual-task draw and pass ability than non-selected players. Skinfold thickness and dual-task draw and pass proficiency were the only variables that contributed significantly (P < 0.05) to the discriminant analysis of selected and non-selected players. These findings suggest that selected physiological, anthropometric, and skill qualities may influence team selection in professional rugby league.